18F-FP-CIT PET/CT in a case of probable sporadic Creutzfeldt-Jakob disease with parkinsonism as initial symptom. Issue 1 (31st December 2022) - Tang, Songhan; Dou, Xiaofeng; Zhang, Ying
ABSTRACT: Creutzfeldt-Jakob disease (CJD) is a low-prevalence, fatal neurodegenerative disease. Parkinsonism as first symptom of CJD is rare. We present a case manifesting difficulty falling asleep as unspecific prodromal symptom and parkinsonism as initial symptom. The patient received positron emission tomography/computed tomography (PET/CT) of dopamine transporter (DAT) using 18 F-FP-CIT. The DAT-scan demonstrated presynaptic dopaminergic deficit in bilateral posterior putamen, which supports the hypothesis of nigrostriatal pathway dysfunction in CJD.